Supply Chain Performance Measurement Using the Scor Model: a Case Study at PT. Perkebunan Nusantara IV Regional V - Muhammad Ihsan; Maswadi Maswadi; Imelda Imelda (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to measure the supply chain performance of PT. Perkebunan Nusantara IV Regional V located in Ngabang District, Landak Regency. The research was conducted purposively over one month with a population of 97 employees, all of whom were included as the sample (census sampling). Data were collected through observation, structured questionnaires, interviews, and documentation review. The analysis employed the Supply Chain Operations Reference (SCOR) model combined with the Analytical Hierarchy Process (AHP). The results indicate that the company’s supply chain performance falls into the excellent category, with a final score of 99.83. All five SCOR processes Plan, Source, Make, Deliver, and Return operate effectively and efficiently. Deliver and Return achieved the highest performance, while Plan and Make showed relatively lower scores, mainly due to challenges in yield prediction and production capacity adjustments. The findings also reveal that priority weights do not always correspond directly to performance outcomes. Overall, the company’s supply chain operates optimally, although improvements are still needed in planning and production aspects.